Myeloperoxidase Deficiency Alters the Process of the Regulated Cell Death of Polymorphonuclear Neutrophils - Kremserová, Silvie; Kocurková, Anna; Chorvátová, Michaela; Klinke, Anna; Kubala, Lukáš (Frontiers in Immunology, 2022)
Polymorphonuclear neutrophils (PMNs) play a key role in host defense. However, their massive accumulation at the site of inflammation can delay regenerative healing processes and can initiate pathological inflammatory processes. Thus, the efficient clearance of PMN mediated by the induction of regulated cell death is a key process preventing the development of these pathological conditions. Myeloperoxidase (MPO), a highly abundant enzyme in PMN granules, primarily connected with PMN defense machinery, is suggested to play a role in PMN regulated cell death. However, the contribution of MPO to the mechanisms of PMN cell death remains incompletely characterized. Herein, the process cell death of mouse PMNs induced by three different stimuli – 12-myristate 13-acetate (PMA), opsonized streptococcus (OST), and N-formyl-met-leu-phe (fMLP) – was investigated. MPO-deficient PMN revealed a significantly decreased rate of cell death characterized by phosphatidylserine surface exposure. An inhibitor of MPO activity, 4-aminobenzoic acid hydrazide, showed only a limited effect on PMA-induced cell death compared to MPO deficiency. Interestingly, the dying activated PMNs did not present the activation of other markers characteristic of apoptotic cell death. On the other side, markers characterizing autophagy such as the cleavage of LC3 protein, the citrullination of histone H3, and its surface expression. Collectively, the ability of MPO to modulate the life span of PMNs can affect the course of inflammation, independently of its putative microbicidal functions.